Quantitative Analysis Of The Meteorological Data And Their ImplicationFor Geo-Environmental Classification Map Of The Nineveh Governorate - AL_Daghastani, Hekmat; Yahya, Basher (Iraqi Journal of Science, 2024)
Given the close interrelationship between the manifestations of geomorphologiclandforms and landuse and landcover on the one hand and quantitative analysis ofthe Meteorological data and its implications on the classification map of theGovernorate of Nineveh, on the other, the present study rely on the basic elementsused in the style of the interpretation of visual multi-data images providing a mainpillar for the diagnosis of some environmental problems, which began to suffer fromNineveh Governorate over time. Evidence suggests many of the elements in theanalysis of climate change for the period (1974-2010) to speed up the processes ofdesertification and environmental budget imbalance of vegetation, which reflectednegatively on the composition of dust storms and their conformity with the currentreality of the geo-environmental classification map for the Governorate.